2020
DOI: 10.1108/sasbe-06-2019-0073
|View full text |Cite
|
Sign up to set email alerts
|

A novel simulation-annealing enabled ranking and scaling statistical simulation constrained optimization algorithm for Internet-of-things (IoTs)

Abstract: PurposeSimulation-based optimization is a decision-making tool for identifying an optimal design of a system. Here, optimal design means a smart system with sensing, computing and control capabilities with improved efficiency. As compared to testing the physical prototype, computer-based simulation provides much cheaper, faster and lesser time-and resource-consuming solutions. In this work, a comparative analysis of heuristic simulation optimization methods (genetic algorithms, evolutionary strategies, simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Many colleges and universities in China have been playing an important role in cultivating producers and graduates who develop relationships in moral, intellectual, physical, aesthetic, social, and other aspects. erefore, vocational training in colleges and universities must adhere to the correct culture [2]. Colleges and universities have always been an important foundation for growing crops and providing skills for national development and prosperity.…”
Section: Introductionmentioning
confidence: 99%
“…Many colleges and universities in China have been playing an important role in cultivating producers and graduates who develop relationships in moral, intellectual, physical, aesthetic, social, and other aspects. erefore, vocational training in colleges and universities must adhere to the correct culture [2]. Colleges and universities have always been an important foundation for growing crops and providing skills for national development and prosperity.…”
Section: Introductionmentioning
confidence: 99%
“…e main way to meet it is to obtain more income [14]. erefore, from the perspective of the capital scale of R&D investment, it should not only make up for the cost of R&D investment but also make the R&D subject have benefits beyond the cost.…”
Section: Methodsmentioning
confidence: 99%
“…For this reasons, acknowledging building information modeling (BIM) as the leading methodology and the common technological ground for the digitization of the construction sector through innovative applications in every industry field (Newman et al , 2020), from real-time sensor integration for thermal efficiency (Birgonul, 2021; Kumar et al , 2020) and implementation of advanced technologies and methodologies for project inspection, documentation and management (Elghaish et al , 2020; Getuli et al , 2021; Götz et al , 2020; Mansuri and Patel, 2021) to multi-purpose integration of the advanced visualization technologies (Alizadehsalehi et al , 2020; Getuli and Capone, 2018; Pour Rahimian et al , 2020), comprising construction and safety management (Getuli, 2020; Getuli et al , 2016, 2017; Martínez-Aires et al , 2018), the authors already identified in previous works the opportunity to foster the administration of VR safety training with the integration of BIM and game technology (Getuli et al , 2018, 2019). Moreover, to demonstrate a large-scale feasibility of immersive VR for workers’ safety training, an implementation protocol for planning, management and administration of HS contents with BIM and VR has been proposed and tested on a real case study project (Getuli et al , 2020).…”
Section: Introductionmentioning
confidence: 99%